A New Way of Managing Canalicular Injury Associated With Late Eyelid Burns. Issue 7 (October 2019) - Ma, Yingjie; Mao, Bangxun; Lan, Shuqin; Chen, Tingting; Yu, Bo
Abstract : Purpose: This study aimed to introduce a new way to rebuild the canalicular system of patients with occluded punctums after long-time burns. Methods: Cases with eyelid burns associated canalicular injury presented at Eye Hospital of Wenzhou Medical University from June 1st, 2015 to September 30th 2017 were referred to department of Orbital & Oculoplastic Surgery. Cases with occluded both superior and inferior punctuns were recommended to surgery. Twenty-seven cases were enrolled in our study. Patients were followed up at 1, 2, and 4 weeks and 3, 4, 6, and 12 months postoperatively. Success of the surgery was defined as being free of epiphora and purulence postoperatively, a normal functional endoscopic dye test, free-flowing irrigation through the lacrimal system, and the presence of upper and lower punctum ostium. Results: With a follow-up of 12 months postoperative, there were 22 cases that showed surgical success outcome according to the set criteria. The success rate of our surgery is 81.48%. Conclusion: The surgical procedure used in our study is an effective and easy way to treat patiens with occluded punctum after long-time burns. The utility of silicone intubation is necessary and delayed tubing removal maybe meaningful in these kinds of patients.